Computational dynamics - Shabana, Ahmed A., 1951- (Chichester, U.K. : John Wiley & Sons, 2010)
'Computational Dynamics, 3rd edition, thoroughly revised and updated, provides logical coverage of both theory and numerical computation techniques for practical applications. The author introduces students to this advanced topic covering the concepts, definitions and techniques used in multi-body system dynamics including essential coverage of kinematics and dynamics of motion in three dimensions. He uses analytical tools including Lagrangian and Hamiltonian methods as well as Newton-Euler Equations'--Resource description page.
Introduction -- Linear algebra -- Kinematics -- Forms of the dynamic equations -- Virtual work and lagrangian dynamics -- Constrained dynamics -- Spatial dynamics -- Special topics in dynamics -- Multibody system computer codes.
Includes bibliographical references and index.
Print version record.
Keywords: Dynamics; Dynamics; Electronic books